SEMIOTIC STUDY OF TIDUNG TRIBE CLOTHING IN THE IRAW TENGKAYU TRADITION IN TARAKAN CITY - Dhani, Santi Asmara; Komariah, Kokom; Hendri, Zulfi (Pena Cendekia Insani, 2026)
This research is based on the phenomenon of the lack of understanding of the people of Tarakan City towards the Tidung tribal clothing in the Iraw Tengkayu tradition. The purpose of the research is to explore the images, symbols, meanings, and philosophical values of the Tidung tribal clothing consisting of everyday clothing, traditional clothing, and formal clothing in the implementation of the Iraw Tengkayu tradition. This research is qualitative research with a Grounded Theory approach and semiotic analysis. Data were collected through interviews, observations, and documentation of five informants selected by the snowball sampling method. The validity of the data was tested through credibility, transferability, dependability, and confirmability, with the application of source and technique triangulation. Data analysis uses the Miles and Huberman model which includes three stages: data reduction, data presentation, and conclusion drawing. The results of the study can reveal the meaning of the Tidung tribal traditional clothing worn more referring to the colors, motifs, and shapes related to the life of the Tidung tribe, and the philosophical values contained in them in the form of social, religious, ethical, and aesthetic values. The recommendations from the results of this study should be a source of information for the public to better know, understand, and play an active role in preserving local culture, and can be used to support the development of MSMEs that produce traditional Tidung clothing in accordance with its symbols, meanings, and philosophical values, which in the end can contribute to the economic development of Tarakan City.